Psychometric Properties of the Social Initiative Scale for Children with Autism Spectrum Disorder - Ali, Sirwan Wali; Farok , Osama Mostafa; Almufti, Birivan Abduiia (Journal of Tikrit University for Humanities, 2024)
The research aims to verify the psychometric properties of the social initiative scale for children with autism spectrum disorder. To achieve this, a random sample of children with autism spectrum disorder was selected, consisting of (80) boys and girls in the city of Erbil, Iraq. The scale includes three dimensions, and the content validity of the scale reached (93.76%), which is a high percentage. The significance of the internal consistency indicators was calculated by calculating the correlation coefficients between the scores of each statement of the scale and the total score of the dimension to which it belongs, and between the dimensions as well and the scale as a whole and their level of significance. The correlation coefficients were high (0.794-0.921) and significant. Statistically at the level of (0.01), the indications of the validity of the interpretations of the scores were calculated through confirmatory factor analysis. The dimension of initiating with peers in the social context was saturated with (3.301) on the general factor, while the component of responding to initiating with others was saturated with (1.804), in When the conversation etiquette component was saturated with (2.608), and the connotations of honesty were used using the test (Al-Dosari, 2010), the correlation coefficients were high and statistically significant at the level of (0.01) between the components of both scales, and the connotations of the scale reliability indicators were calculated using the Cronbach alpha method (0.856): The Guttman coefficient (λ2) (0.864), the Guttman coefficient (λ6) (0.922), and the McDonald coefficient (0.859). The results showed that the social entrepreneurship scale has good psychometric properties and is valid for application to this group